A next-generation-sequencing panel for mutational analysis of dominant acute hepatic porphyrias. (4th July 2019) - Barman-Aksözen, Jasmin; Suter, Lukas; Wegmann, Franziska; Meienberg, Janine; Minder, Anna Elisabeth; Beer, Marc; Komminoth, Paul; Minder, Elisabeth I.; Schneider-Yin, Xiaoye
Abstract: Molecular diagnosis of autosomal dominant acute hepatic porphyrias (AHPs) plays an important role in the management of these disorders. To introduce next generation sequencing (NGS) to the porphyria diagnosis, we designed a panel that contained four genes, ALAS1, HMBS, CPOX and PPOX for mutational analysis of acute intermittent porphyria (AIP), hereditary coproporphyria (HCP) and variegate porphyria (VP). To validate the AHP panel, 30 samples with known pathogenic variants as determined by Sanger sequencing, were analyzed using the Ion PGM™. Among them, nine have so far not been reported. The pathogenic variants were identified and annotated manually in IGV by three individuals who were blinded to the Sanger results. The AHP panel consists of 95 amplicons that covers 92% of the coding region of the four genes. Of the 95 amplicons, 93 had an average read-depth of >500 reads. In 29 of the 30 tested samples, pathogenic variants were correctly identified and annotated. The number of reads from the mutated alleles were approximately 50% of the total. The annotation of a 22-bp duplication with NGS differed from that of Sanger by one nucleotide. NGS showed an advantage in allelic discrimination over Sanger sequencing and was also able to detect a known somatic variant in the HMBS gene. The AHP panel will be applied in the initial diagnosis of new patients. Any sequence variations with a frequency of ≥10% will be confirmed by Sanger sequencing. The cost-effectiveness of a NGS approach for AHP in a diagnostic laboratory needs to be further assessed.